Fiscal Federalism, Public Capital Formation, and Endogenous Growth - Liutang Gong; Heng-fu Zou (Annals of Economics and Finance, 2003)
This paper extends the Barro (1990) growth model with one aggregate government spending and one flat income tax to include federal and local public consumption, federal and local public capital formation, federal and local taxes, and federal transfers to locality. It derives the rate of endogenous growth and examines how the growth rate and welfare respond to changes in federal taxes, local taxes, and federal transfers.